Review on Current Status of Echinocandins Use - Martyna Mroczyńska; Anna Brillowska-Dąbrowska (MDPI AG, 2020)
Fungal infections are rising all over the world every year. There are only five medical compound classes for treatment: triazoles, echinocandins, polyenes, flucytosine and allylamine. Currently, echinocandins are the most important compounds, because of their wide activity spectrum and much lower sides effects that may occur during therapy with other drugs. Echinocandins are secondary metabolites of fungi, which can inhibit the biosynthesis of β-(1,3)-D-glucan. These compounds have fungicidal and fungistatic activity depending on different genera of fungi, against which they are used. Echinocandin resistance is rare-the major cause of resistance is mutations in the gene encoding the β-(1,3)-D-glucan synthase enzyme. In this review of the literature we have summarized the characteristics of echinocandins, the mechanism of their antifungal activity with pharmacokinetics and pharmacodynamics, and the resistance issue.